Penguasaan Tubuh Perempuan Oleh Budaya Patriarki Dalam Film Yuni - Tania Zahirah Salwa; Sulih Indra Dewi; Asfira Rachmad Rinata (Lenvari: Journal of Social Science, 2023)
Patriarchal culture tends to exclude women, can bring up various social problems that shackle women’s freedom and curb the rights that women should have. This is what causes discrimination against women, especially against women’s bodily autonomy. This social reality is often raised in a media, especially a film. One of the films with the theme of women living in patriarchal shackles is Yuni’s film. The purpose of this study is to determine the mastery of women’s bodies by the patriarchal culture contained in Yuni’s film using the concept of critical discourse analysis by Norman Fairclough. According to Norman, the discourse in this film can be in form of text analysis, discursive practice, and socio-cultural practice. The type of research used is descriptive qualitative with approach Critical Discourse Analysis (CDA) in order to reveal more deeply the mastery of women’s bodies by patriarchal culture in Yuni’s film. The results of this study reveal that there are three forms of mastery over women’s bodies by patriarchal culture in Yuni’s film, namely (1) control over sexuality, (2) control over reproduction, and (3) control over movement space.